Das Lebensende in der Schweiz - Zimmermann, Markus (Schwabe Verlag, 2019)
This volume gives an overview of what is known from an academic perspective about the end of life in Switzerland. The authors, who represent different academic disciplines, deal with crucial questions, such as experiences of individuals, personal decisions concerning their own end of life, care situations, costs, legal regulations, and ideals of dying.